The Call to Poetry: Poems from Pre-Independence Singapore. Ed. Rosaly Puthucheary. - Yoong, Regina (SARE: Southeast Asian Review of English, 2023)
Book Review for The Call to Poetry: Poems from Pre-Independence Singapore. Ed. Rosaly Puthucheary.